The Laboratory Investigations and Diagnosis of Viral Diseases (International Journal of Food and Nutritional Sciences, 2022)
The proper management of viral infections entails accurate diagnosis of viral diseases and their modes of transmission; as a result, appropriate treatment modalities are applied. Additionally, it improves clinicians' abilities to decide on the best course of action for patients, monitor disease progression, and avoid overusing antibiotics. Understanding the pathogen also aids in understanding infection control and the success rate of antiviral therapies, both of which affect the prognosis of patients. For early intervention of a particular viral condition, specific nucleic acid and serological testing for various viral infections is crucial. However, these tests should be complemented by the continuing use of serology in cases of chronic infections or viruses with brief viremia. This article gives a quick overview of recent advancements in diagnostics that could soon increase our ability to provide a definitive diagnosis. Clinical specimens must always be tested in the lab for the presence of virus, viral antigens, or particular antibodies and specificity in order to make an accurate virus diagnosis